THE SOCIO-ASSISTANCE SURVEILLANCE FUNCTION AS AN ENABLER OF SOCIAL PROTECTION IN THE SOCIAL ASSISTANCE POLICY (Editora Impacto Científico, 2025)
This article aims to reflect on the importance of the role of socio-assistance surveillance as a potentiator of social protection in the Social Assistance Policy, bringing elements that conceptually underpin the construction of Socio-assistance Surveillance positioning as a strategic field of strengthening and improvement of Social Assistance as an instance of social protection. The research in terms of objectives was explanatory and in terms of its procedures had in the bibliographic research, the fruitful field of survey and discussion of the various literatures on social assistance and Socio-assistance Surveillance. It was pointed out in the theoretical reflection the primordial role of the function of Surveillance in the guarantee of social protection in the assistance policy and how it becomes primordial to overcome, as analysis and systematization of reality, the residual Matrix of social protection standard in the neoliberal context, strengthening the production of knowledge for the guarantee and expansion of social protection coverage.